(untitled) (Palimpsesto, 2023)
We propose that based on the reading of the literary corpus “Ciudad Cero” (2020) by Elvira Hernández, Décimas del Estallido(2020) by Nano Stern and “Cambio Cambio Cambio” (2020) by Ivania Espejo we can identify some keys that allow us to develop a reading of the poetic production that emerged from the eaves of the social outbreak from certain neo-avant-garde frameworks, understanding it as the irruption of a language capable of confronting the supports of the structures of power, and making visible, in an art-political commitment, dissidence, marginality and the bodies hitherto invisible